10-mm versus 5-mm umbilical port in laparoscopic cholecystectomy: A comparative study in a medical college in Eastern India - Subhadip Sarkar,; Biswarup Bose,; Banyeswar Pal, (Asian Journal of Medical Sciences, 2022)
Background: Laparoscopic cholecystectomy (LC) the most common laparoscopic surgery performed worldwide. The surgical technique of LC has undergone many modifications; in respect to reduction of port sizes or number of ports. Conventionally, 10-mm 30° laparoscope is being used but, 5-mm 30° laparoscopes through 5-mm umbilical port (modified LC) are also being utilized by many surgeons worldwide. Aims and Objectives: The aims of this study were to compare the outcome of conventional LC with modified LC, in terms of feasibility, safety, and efficacy. Materials and Methods: This prospective randomized study was carried out in the Department of Surgery, ESIC-PGIMSR, Joka during June 2017–December 2018. One hundred and fifty patients of diagnosed symptomatic gall stone disease were randomly allocated into two study groups. Group-I contained 75 patients, who underwent LC by conventional method whereas, and 75 patients in Group-II underwent LC by modified method. Follow-up was done at 6 weeks, 6 months, and 1 year after surgery. Data were analyzed by appropriate statistical tests. Results: The mean operating time and mean pain score over umbilical wound were found to be statistically significant. However, no significant differences were obtained in terms of average hospital stay, post-surgical complications such as post-site bleeding, cystic artery bleeding, biliary spillage, and wound infection. Only one patient in the 10-mm umbilical port group, having body mass index of 31 developed umbilical port-site hernia. Regarding wound cosmesis, no significant difference was obtained. Conclusion: Performing LC with a 5-mm 30° laparoscope through 5-mm umbilical port is a safe and feasible option for laparoscopic surgeons.